Advances of Zebrafish in Neurodegenerative Disease: From Models to Drug Discovery - Xiaobo Wang; Xiaobo Wang; Jin-Bao Zhang; Jin-Bao Zhang; Kai-Jie He; Fen Wang; Chun-Feng Liu; Chun-Feng Liu; Chun-Feng Liu (Frontiers Media S.A., 2021)
Neurodegenerative disease (NDD), including Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis, are characterized by the progressive loss of neurons which leads to the decline of motor and/or cognitive function. Currently, the prevalence of NDD is rapidly increasing in the aging population. However, valid drugs or treatment for NDD are still lacking. The clinical heterogeneity and complex pathogenesis of NDD pose a great challenge for the development of disease-modifying therapies. Numerous animal models have been generated to mimic the pathological conditions of these diseases for drug discovery. Among them, zebrafish (Danio rerio) models are progressively emerging and becoming a powerful tool for in vivo study of NDD. Extensive use of zebrafish in pharmacology research or drug screening is due to the high conserved evolution and 87% homology to humans. In this review, we summarize the zebrafish models used in NDD studies, and highlight the recent findings on pharmacological targets for NDD treatment. As high-throughput platforms in zebrafish research have rapidly developed in recent years, we also discuss the application prospects of these new technologies in future NDD research.